PERAN KEPALA SEKOLAH DALAM MEWUJUDKAN GENERASI MANDIRI SERTA BERAKHALAKUL KARIMAH DI SMP IT ATSAQIBIYAH DAN MTS AL-IKHLAS BONTANG - Irsyad, Irsyad (STIT Al-Ittihadiyah Labuhanbatu Utara, 2023)
In the evolving era of increasing freedom, it has had an impact on the behavior of the Indonesian youth. Therefore, the role of schools becomes crucial in shaping and maintaining the behavior of the youth in accordance with noble values. In this context, the role of the school principal becomes highly significant in keeping up with these conditions. Hence, this research aims to identify the Role of the School Principal in Fostering Self-Reliant and Morally Upright Generations in two educational institutions, namely SMP IT Atsaqibiyah in Bontang City and MTs Al-Ikhlas in Bontang. This research is a qualitative study with a multi-site studies approach. Data collection techniques include observation, documentation, and interviews. Data presentation is categorized based on the elements of the school principal's role. Data analysis is conducted using an interactive method consisting of data condensation, data presentation, and drawing conclusions. Data validity is ensured through the extension of participation and researcher persistence tests. The research findings indicate that the Principal of SMP IT Atsaqibiyah in Bontang City plays the role of an effective manager, an administrator managing various aspects of the school, a supervisor providing guidance, a leader leading with leadership qualities, an innovator creating innovative learning environments, and a motivator fostering a motivating school community. Meanwhile, the Principal of MTs Al-Ikhlas in Bontang City has the role of a manager who integrates religious values, an administrator who establishes rules and regulations based on religious values, a supervisor who monitors the application of religious teachings, a leader in achieving religious educational goals, an innovator who stimulates creativity in religious education, and a motivator who motivates teachers and students to achieve religious educational goals. The main obstacles to fostering self-reliant and morally upright generations in both schools include students' lack of awareness of rules and regulations, negative environmental influences, challenges in implementing moral values, students' absenteeism from religious practices, and a lack of religious understanding. Solutions implemented include a proactive approach, close collaboration with parents and teachers, and the implementation of character development programs.